The hypotyresis in patients with chronic obsructive pulmonary disease (COPD) - N. A. Matsegora; O. E. Shpota (Kazimierz Wielki University, 2018)
The processes of reparative regeneration of the bronchial epithelium are controlled by thymic factors, thyroid hormones, and cellular immunity in patients with COPD in a stage of exacerbation. It complicates by purulent necrotic of the bronchopulmonary system amid a decrease of reduce synthesis of endogenous triiodothyronine. We gave pathophysiological rationale for use of thyroid hormone replacement therapy for correction of hormone (thymalin and thyroid -) dependent functional activity of lymphocytes. We proved the clinical effectiveness of the using alternative triiodothyronine therapy as an extra-immune immunocorrector. It includes thyroid and thymalin-dependent effects in patients with COPD with low triiodothyronine syndrome in the period of exacerbation.